Geraniol attenuates hydrogen peroxide-induced liver fatty acid alterations in male rats - Ozkaya, Ahmet; Sahin, Zafer; Gorgulu, Ahmet Orhan; Yuce, Abdurrauf; Celik, Sait (Ejmanager Llc, 2017)
Background: Hydrogen peroxide (H2O2) is an oxidant agent and this molecule naturally occurs in the body as a product of aerobic metabolism. Geraniol is a plant-derived natural antioxidant. The aim of this study was to determine the role of geraniol on hepatic fatty acids alterations following H2O2-induced oxidative stress in male rats. Methods: After randomization, male Wistar rats were divided into four groups (n = 7 each group). Geraniol (50 mg/kg, dissolved in corn oil) and H2O2 (16 mg/kg, dissolved in distilled water) were administered by an intraperitoneal injection. Administrations were performed during 30 days with 1-day interval. Results: Administration of H2O2 resulted with a significant increase in malondialdehyde (MDA) and a significant decrease in glutathione (GSH) peroxidase glutathione level; geraniol restored its effects on liver. However, hepatic catalase (CAT) activities were significantly higher in H2O2, geraniol, and geraniol+ H2O2 groups than control group. The ratio of hepatic total saturated fatty acids increased in H2O2-treated animals compared with control. In addition, hepatic total unsaturated fatty acids reduced in H2O2 group compared with control. The percentages of both hepatic total saturated and unsaturated fatty acids were not different between geraniol+ H2O2 and control groups. Conclusions: H2O2-induced oxidative stress may affect fatty acid composition in liver and body. Geraniol can partly restore oxidative hepatic damage because it cannot completely reverse the H2O2 -induced increase in hepatic CAT activities. Moreover, this natural compound can regulate hepatic total saturated and unsaturated fatty acids percentages against H2O2-induced alterations.
Keywords: Fatty acids; geraniol; hydrogen peroxide; liver; oxidative stress